ERASMUS Students Experiences in Linguistic Diversity and Multicultural Communication - Užpalienė, Daiva; Vaičiūnienė, Vilhelmina (Verbum, 2012)
The promotion of students’ mobility in the EU has had a huge impact in recent years in Lithuania, which has now become one of the countries with more students going abroad on an ERASMUS programme. Apart from being a means of studies and communication, languages offer access to cultural knowledge, diverse social and cultural identities and also contribute to cross-cultural communication both within Europe and with the rest of the world. The experiences gained while studying and living in another country give students a better sense of what it means to be a European citizen. The paper presents an analysis of the survey findings into MRU Erasmus Exchange students’ (20 respondents) reflections and communication experience through different languages in multicultural environment in host countries. The survey focuses both on students’ benefits and challenges they have encountered while applying their knowledge and language skills in the study process and everyday communication.